Understanding the Immune System in Fetal Protection and Maternal Infections during Pregnancy. (24th June 2022) - Hussain, Tarique; Murtaza, Ghulam; Kalhoro, Dildar Hussain; Kalhoro, Muhammad Saleem; Yin, Yulong; Chughtai, Muhammad Ismail; Tan, Bie; Yaseen, Anjaleena; Rehman, Zia Ur
Abstract : The fetal-maternal immune system determines the fate of pregnancy. The trophoblast cells not only give an active response against external stimuli but are also involved in secreting most of the cytokines. These cells have an essential function in fetal acceptance or fetal rejection. Other immune cells also play a pivotal role in carrying out a successful pregnancy. The disruption in this mechanism may lead to harmful effects on pregnancy. The placenta serves as an immune barrier in fetus protection against invading pathogens. Once the infections prevail, they may localize in placental and fetal tissues, and the presence of inflammation due to cytokines may have detrimental effects on pregnancy. Moreover, some pathogens are responsible for congenital fetal anomalies and affect almost all organs of the developing fetus. This review article is designed to address the bacterial and viral infections that threaten pregnancy and their possible outcomes. Moreover, training of the fetal immune system against the exposure of infections and the role of CD49a + NK cells in embryonic development will also be highlighted.